Fitting the Evolution of COVID-19 Cases of China and Thailand by Applying Piecewise Linear Approximation of Compartmental Model Parameters - Kiravittaya, Suwit (Asian Health, Science and Technology Reports, 2020)
This article explains an improved method to fit the evolution dynamics of the COVID-19 pandemics in China and Thailand during January – April 2020. It is done by using a conventional compartmental model and piecewise linear approximation of the model parameters. The reported COVID-19 data of China between 22nd January and 22nd March (60 days) and Thailand between 14th March and 16th April (34 days) are considered. According to the evolution trends, estimations on the total numbers of population involved in the spreading are made and they are about 83000 for China and 3000 for Thailand. By further analyzing the data along with the Susceptible-Infected-Recovered model, relevant epidemiological parameters, which indicate the degree of the outbreak, can be extracted. For the China data, a good fit is obtained when linear time-varying functions for the parameters are assumed. In case of Thailand data, a reasonable fit is obtained with constant parameter values and it can be improved by considering the time lag of 13 days before the triggering of the recovery rate. Based on the obtained model parameters, a forecast of epidemic situation in Thailand is made. The expected end point of critical pandemic period is at the mid of June 2020. The calculated basic reproduction number of 3.39 is reported for the epidemic spreading of COVID-19 in Thailand.